[OP.2A.07] RNASEQ STUDY OF SALT STRESS PATHWAYS IN RENAL TUBULE REVEALS INCREASED EXPERSSION OF HEAT SHOCK GENES INVOLVED IN SALT SENSITIVE HYPERTENSION. (September 2017) - Graham, L.; Aman, A.; Campbell, D.; Dominiczak, A.; Padmanabhan, S.
Abstract : Objective: Among the environmental factors that contribute to hypertension, excessive salt intake is the most common and important risk factor. Although, the specific pathways involved in salt tolerance in the renal tubules is not well defined, metabolomic studies in bacteria, yeasts, and human cell lines report lower glycolysis, tricarboxylic acid cycle, branched-chain amino acid metabolism and heme biosynthesis responding to salt challenge. However, to date there are no studies on transcriptome response in renal tubules to salt stress. Here we aimed to delineate the hyperosmotic salt stress pathways in renal tubules. Design and method: Thick Ascending Limb (TAL) tubules were isolated from sv129 mice, and treated with NaCl (300mOsMol) or no treatment (n = 3 per group). Total RNA was isolated and RNA-Seq performed using the NextSeq 500 platform operating 2*75 bp paired end cycles (33 million reads per sample). Raw read files were adapter trimmed and quality filtered using Cutadapt, to produce reads with mean quality score no less than 20 using Sanger quality scores. Differentially expressed genes were identified using the DESEQ2 R package, and significant pathways identified using Gene Set Analysis (GSA). Genes for PIANO enrichment were accepted as differentially expressed if the adjusted p-values calculated using DESEQ2 were less than 0.01. Significant pathways were identified as those where the Benjamini-Hochberg adjusted p-values were below a threshold of 0.05, at a false detection rate of 0.1. Results: Twelve genes were significantly associated with the salt stress treatment. Heat maps revealed an up regulation of heat shock genes and a down regulation of drug membrane transport genes during salt loading. Gene set enrichment revealed the greatest changes occurred in the expression of two heat shock genes: Hspa1a (Log2 fold change 4.35, p = 2.48e–12) and Hspa1b (Log2 fold change 4.05, p = 2.48e–12). Conclusions: Our results are the first to show that hyperosmotic salt stress in renal tubules alters the transcriptome, leading to an over expression of heat shock genes in the kidney. These genes have been shown to increase NaCl reabsorption and urea content in the medullary region of the kidney, contributing to salt sensitive hypertension.